Analysis of Business Use Right (HGU) by the North Sumatra Province National Land Agency (BPN), and Salvation of State Assets on Abandoned Lands through Communication (Negotiation) - Al-Hafidh, Muhammad Najmu (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This research aims to identify (1) the factors causing land abandonment (HGU), (2) the role of the National Land Agency (BPN) in carrying out its authority and institutions. and (3) BPN's negotiation communication efforts in managing abandoned land. This research was conducted at the regional office of the National Land Agency of North Sumatra Province. The method used in the research is a qualitative descriptive method in which the selection of sources or informants is carried out deliberately. Data collection was collected through observation, in-depth interviews, and documents. The research results show that the factors causing the abandonment of Business Use Rights (HGU) include technical business management factors and socio-economic factors. So the role of BPN is to carry out the authority and mechanism for managing abandoned land as an institution that has the authority to prepare all forms of data and facts, including those found based on the results of land surveys as important documents needed in handling abandoned land. through the applicable mechanism. Communication (negotiation) efforts in managing abandoned land include communication (negotiation) with farming communities by conducting face-to-face dialogue to discuss consensus by applying an existent approach. existent, group approach, and formal/bureaucratic approach through socialization and participation of village community leaders and officials. In addition, carry out communication efforts (negotiations) with related agencies/parties by coordinating to achieve common goals in the public interest so that they have a common perception and model for obtaining economic benefits. economics of the resource economy in the HGU area.